Does preservative content affect drug permeability? The permeability analysis in vitro of 3 ophthalmic Latanoprost formulations in a human epithelial cell culture model - Romaniuk, Dorota; Smagur, Jan; Cisek, Agnieszka; Antonik, Justyna; Romaniuk, Wanda (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Aim : Comparative permeability analysis of the 3 following Latanoprost formulations intended for ophthalmic use: Xaloptic (Polpharma S.A.), Xalatan (Pfizer Europe MA EEIG) and Monoprost (Thea Pharma S.A.) across human corneal epithelium (HCE-T culture model) in vitro. Material and methods : Permeability analysis was performed under conditions suitable for latanoprost API (active pharmaceutical ingredient). Statistical analysis of permeability and drug quantity after passing across a cellular membrane was performed using ANOVA test and Tukey’s multiple comparison test (GraphPad Prism 6.00 for Windows, GraphPad Software, La Jolla California, USA). Results : The following differences in permeability were noted between the analyzed drugs: The permeability rates for Xaloptic and Xalatan were 5.49 ± 1.64 x 10-6 cm/s and 4.66 ± 1.13 x 10-6 cm/s, respectively. Xaloptic showed the highest permeability through human corneal epithelium (23.70 ± 1.71 x 10-6 cm/s) and the highest conversion rate (28.13 ± 5.85%). As compared to Xaloptic, Xalatan slight, yet statistically significant differences with the permeability rate of 21.21 ± 1.29 x 10-6 cm/s and a conversion rate of 18.41 ± 2.96%). Monoprost demonstrated the lowest permeability (0.39 ± 0.07 x 10-6 cm/s) and the lowest conversion rate (0.34 ± 0.16%). Conclusion : The differences in permeability and bioavailability between the 3 ophthalmic latanoprost formulations are attributable to the differences in their composition. They are also related to the content of preservative in each preparation.